Highlights in pathogenic fungal biofilms - Orlandi Sardi, Janaina De Cassia [UNESP]; Pitangui, Nayla De Souza [UNESP]; Rodriguez-Arellanes, Gabriela; Lucia Taylor, Maria; Fusco-Almeida, Ana Maria [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Asociacion Espanola Micologia-aem, 2014)
A wide variety of fungi have demonstrated the ability to colonize surfaces and form biofilms. Most studies on fungal biofilms have focused on Candida albicans and more recently, several authors have reported the involvement of other genera of yeasts and Candida species, as well as of filamentous fungi in the formation of biofilms, including: Cryptococcus neoformans, Cryptococcus gattii, Rhodotorula species, Aspergillus fumigatus, Malassezia pachydermatis, Histoplasma capsulatum, Paracoccidioides brasiliensis, Pneumocystis species, Coccidioides immitis, Fusarium species, Saccharomyces cerevisiae, Trichosporon asahii, Mucorales and Blastoschizomyces. There is a current interest in describing the particular characteristics of the biofilm formation by of these fungi. A major concern is the control of biofilms, requiring knowledge of the biofilm mechanisms. However, our knowledge of these microbial communities is limited, due to the complexity of these systems and metabolic interactions that remain unknown. This mini-review aims to highlight recently discovered fungal biofilms and to compare them with the current knowledge on biofilms.This manuscript is part of the series of works presented at the V International Workshop: Molecular genetic approaches to the study of human pathogenic fungi (Oaxaca, Mexico, 2012). (C) 2013 Revista Iberoamericana de Micologia. Published by Elsevier Espana, S.L. All rights reserved.
Keywords: Biofilm; Quorum sensing; Pathogenic fungi; Adhesins; Anti-biofilm therapy